2010
DOI: 10.1007/s11999-010-1254-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood Culture Flasks for Culturing Synovial Fluid in Prosthetic Joint Infections

Abstract: Background Identifying the etiologic microorganism is essential to guide antimicrobial therapy in prosthetic joint infection. Questions/purpose We (1) compared the frequency of positive cultures with synovial fluid inoculated in blood culture flasks (SF) with those of periprosthetic tissues or swabs in traditional cultures from patients with acute and chronic prosthetic joint infections (PJI) and (2) determined the sensitivity, specificity, and predictive values of the three methods. Patients and Methods We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(95 citation statements)
references
References 13 publications
2
89
2
2
Order By: Relevance
“…A lack of definitive data confirming the best method to isolate pathogens has led to a wide variety of techniques being utilized in evaluating periprosthetic material for infection [1][2][3]6]. While periprosthetic tissue and fluid samples are considered the ideal specimens by some authors [3,6,18], swab cultures continue to be used due to their ease of use and low cost [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of definitive data confirming the best method to isolate pathogens has led to a wide variety of techniques being utilized in evaluating periprosthetic material for infection [1][2][3]6]. While periprosthetic tissue and fluid samples are considered the ideal specimens by some authors [3,6,18], swab cultures continue to be used due to their ease of use and low cost [27].…”
Section: Discussionmentioning
confidence: 99%
“…Font-Vizcarra et al [6] compared the accuracy of synovial fluid cultures, tissue cultures, and swab cultures for diagnosing PJI and concluded synovial fluid cultured in blood culture flasks had higher sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) than the other two culture methods. However, that study used unique clinical criteria for defining infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the available tests for diagnosis of PJI are far from perfect. Cultures, for example, are negative in 7% to 12% of patients with PJI [5,10,16,19]. Culture-negative PJI can potentially complicate case classification and management and is an additional source of stress for both the patient and surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…results. Although not clearly defined, multiple authors have reported rates of culture-negative periprosthetic infection of the hip and knee ranging from 7% to 12% [1,5,8,10,[16][17][18]. The chance that our results were affected by falsenegative culture results is somewhat offset by the fact that all 27 patients had two sets of cultures that were concordant; the aspirate cultures matched the intraoperative culture results for all patients (those who were infected and those who were not).…”
Section: Discussionmentioning
confidence: 85%
“…Stated otherwise, if the nucleated cell count is within normal limits, PJI can be ruled out; nucleated cell count could thus serve as an important screening test in patients where clinical suspicion of infection exists. However, the documented false-negative culture rate of 7% to 12% [1,5,8,10,[16][17][18] makes it difficult to exclude PJI based on this test alone. The false-negative rate of 0% in the current study is likely related to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%